Penerapan Manajemen Pelayanan Publik Berbasis QRIS dan Dampaknya pada Efektivitas Pembayaran PBB P-2 di Kabupaten Gorontalo - Ramadhan Djahidi, Ahmad; Abdussamad, Juriko; Tohopi, Rustam (PROVIDER JURNAL ILMU PEMERINTAHAN, 2025)
Rural and Urban Land and Building Tax (PBB-P2) payments still face obstacles in the form of slow administrative processes, limited access, and low public digital literacy. To address these issues, the local government has begun implementing a Quick Response Code Indonesian Standard (QRIS)-based payment system. This study aims to analyze QRIS-based public service management in PBB-P2 payments at the Regional Revenue Agency (Badan Pendapatan Daerah) of Gorontalo Regency based on the principles of New Public Management (efficiency, effectiveness, transparency, accountability, professionalism, and responsiveness). The method used is descriptive qualitative with informants from the Regional Revenue Agency (Badan Pendapatan Daerah) employees and taxpayers, through interviews, observation, and documentation techniques. The results show that the implementation of QRIS improves administrative efficiency, accelerates transactions, and expands payment access. Transparency and accountability are strengthened through digital footprints, while professionalism is enhanced through human resource training. However, effectiveness remains limited due to low digital literacy and infrastructure, and responsiveness to user complaints needs to be improved. In conclusion, QRIS contributes positively to public service innovation, although it still requires strengthening in terms of literacy and technological support.